(12-4i)(3+i)=0

Simple and best practice solution for (12-4i)(3+i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12-4i)(3+i)=0 equation:


Simplifying
(12 + -4i)(3 + i) = 0

Multiply (12 + -4i) * (3 + i)
(12(3 + i) + -4i * (3 + i)) = 0
((3 * 12 + i * 12) + -4i * (3 + i)) = 0
((36 + 12i) + -4i * (3 + i)) = 0
(36 + 12i + (3 * -4i + i * -4i)) = 0
(36 + 12i + (-12i + -4i2)) = 0

Combine like terms: 12i + -12i = 0
(36 + 0 + -4i2) = 0
(36 + -4i2) = 0

Solving
36 + -4i2 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -36 + -4i2 = 0 + -36

Combine like terms: 36 + -36 = 0
0 + -4i2 = 0 + -36
-4i2 = 0 + -36

Combine like terms: 0 + -36 = -36
-4i2 = -36

Divide each side by '-4'.
i2 = 9

Simplifying
i2 = 9

Take the square root of each side:
i = {-3, 3}

See similar equations:

| c(ad)+x=bd+ad(yz) | | 5x^2=9x-5 | | 360-2x=100 | | 22n=100 | | -10y-3=7y | | (2abc)(-3abc)(-5a)= | | Y=30x+.10 | | -6v+2=1 | | xsquared-7x=-3 | | -6v+2=11 | | 49=2y+17 | | 5(2-4)=30 | | (2abc)(-3abc)(-5)= | | 2x(x+3)-3(2x-3)= | | x^3+-10x+25=0 | | (4v+1)(3+v)=0 | | x^3-10x+26=0 | | 2(x+1)=4x+2 | | 2y-24x=10 | | -2x^2-2x-12=0 | | -2=3y+7 | | -2x-9y=1 | | 36y=1 | | 28+24p=36p | | 2x^3-6x^2-x=0 | | a^3b^2(3a^2b)= | | 6-(3x-6)=7x-9 | | log(7)1= | | Log(x+12)-log(x)=1 | | 9-(2-3)-[3-(5-2)]-[2+(4-3)]= | | 46=3x+2y | | 2x^4-6x^3-x^2+3x=0 |

Equations solver categories